2021
DOI: 10.31234/osf.io/8d3nb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-Analytic Findings in the Self-Controlled Motor Learning Literature: Underpowered, Biased, and Lacking Evidential Value

Abstract: The self-controlled motor learning literature consists of experiments that compare a group of learners who are provided with a choice over an aspect of their practice environment to a group who are yoked to those choices. A qualitative review of the literature suggests an unambiguous benefit from self-controlled practice. A meta-analysis was conducted on the effects of self-controlled practice on retention test performance measures with a focus on assessing and potentially correcting for selection bias in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…In our experiment, the estimated effect size of self-controlled versus yoked (collapsed across our Traditional and Explicit Yoked groups) was g = 0.22. While this estimate is larger than those from the weight-function model and PEESE method, it does fall within the range of plausible effect sizes (McKay et al, 2021). When the lack of a self-controlled advantage in previous work and our current experiment are contextualized within the findings of this recent meta-analysis, it is not as surprising that the so-called self-controlled learning benefit was not replicated.…”
Section: Self-controlled Practice Conditions As Autonomysupportivesupporting
confidence: 48%
See 3 more Smart Citations
“…In our experiment, the estimated effect size of self-controlled versus yoked (collapsed across our Traditional and Explicit Yoked groups) was g = 0.22. While this estimate is larger than those from the weight-function model and PEESE method, it does fall within the range of plausible effect sizes (McKay et al, 2021). When the lack of a self-controlled advantage in previous work and our current experiment are contextualized within the findings of this recent meta-analysis, it is not as surprising that the so-called self-controlled learning benefit was not replicated.…”
Section: Self-controlled Practice Conditions As Autonomysupportivesupporting
confidence: 48%
“…Ultimately, our results add to a growing body of evidence that questions whether autonomy-supportive manipulations directly affect learning. One explanation for this lack of replicability is that the "true" effect of such manipulations are much smaller than previously estimated (McKay et al, 2021). Given the resources required (in terms of sample size) to reliably detect the tiny effects, we encourage motor learning scientists to invest their limited resources carefully-either studying practice conditions that have much bigger effects or devising ways to reduce variability and increase power through clever experimental design (McClelland, 2000).…”
Section: Self-controlled Practice Conditions As Autonomysupportivementioning
confidence: 99%
See 2 more Smart Citations
“…the probability that any given study that has been conducted (published or not) would produce a significant result, termed the expected discovery rate (EDR). The delayed retention time point was considered the primary target for a significant finding in motor learning research and previous research has found substantial selection at that time point (McKay, Yantha, Hussien, Carter, & Ste-Marie, 2021). As such, we focused both the RoBMA and z-curve analyses on delayed retention results.…”
Section: Selection Bias Assessmentmentioning
confidence: 99%